Smart Monitoring System Room Temperature Server Based on Iot Using Http Communication Protocol Method at Xyz University - Sari, Aisah Nur Endah (LPPM STMIK Mardira Indonesia, 2025)
XYZ University, which relies on servers for administrative and academic functions, continues to employ manual temperature monitoring through physical site visits to the server locations. This method presents a risk of delayed response to temperature fluctuations, which could lead to operational issues and data loss. This project aims to establish a real-time temperature monitoring system for server rooms, utilizing IoT and employing the HTTP protocol for communication. The evaluation concentrates on assessing the latency of the HTTP protocol and the dimensions of data packets to verify the system's efficacy in real-time monitoring. The deployment of this intelligent monitoring system is expected to enhance the effectiveness of temperature regulation in server rooms and reduce the risk of damage from overheating. The research findings demonstrate that combining IoT with the HTTP protocol yields a more efficient, anticipatory, and sustainable temperature monitoring solution. Recommendations for future development include the integration of additional protocols, such as MQTT, CoAP (Constrained Application Protocol), or WebSocket.